Contextual-Based Bulletin as Media for Learning Renewable Energy - Susetyo, Gayuh; Sarwanto, Sarwanto; Sukarmin, Sukarmin (Universitas Negeri Surabaya, 2024)
Physics is a science that teaches about physical phenomena. To make it easier for students to learn physics in the Merdeka curriculum, appropriate media for learning.